The effect of fenugreek seeds graecumefoemum Trigonellaas additives to food on some of the biological characteristics of common carp CyprinuscarpioL fish - M. J Alalkawy; Y. J. Namah; E. S. Khamees; A. AL-S. Maruosh; T.S. Hussaen (Journal of Madenat Alelem University College, 2015)
The research was conducted at the center for animal resources and fisheries in Zafaraniyah to investigate the effect of adding fenugreek seeds on the diets of common carp fishCyprinuscarpio L. (80) fishes of incised weight (38 ± 2) g , randomly distributed on five transactions in tow replicate for each treatments, first treatment considers control transactions and the other four contain 1 % 0.2 % 0.3 % and 4 % of fenugreek seeds powder, respectively. The experiment lasted four months, starting from February 2013. Results showed a significant increase (P <0.05) in some growth parameters like the weight gain , relative growth rate and food conversion rate where the transaction (3%) were (15.31 ± 0.28) g / fish , ( 12:28 ± 0.12)% and (4.36 ± 0.13), respectively. While, the percentage of protein efficiency reach the highest value in (4%) to reach (25.39± 0.24)%, also the level of fenugreek seeds in the diets of fish common carp have reached the highest at treatment (4%) for each of the red blood cells (1.75 × 610 ± 0.048), white blood cells (22.86 × 310 ± 0.06), the packed cells volume (31.16 ± 0.10)% and the amount of hemoglobin (10.2 ± 1.19) g / 100 ml of blood.